Pengaruh Budaya Kerja Terhadap Kinerja Pegawai di Puskesmas Krembangan Selatan - Yusriyah, Yusriyah; Mamesah, Marline Merke; Tjokro, Silvia Haniwijaya; Rukmini, Rukmini (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2024)
Background: Work culture is a series of attitudes and behaviors that are part of person’s lifestyle at work. This research was motivated by the existence of obstacles indicating that the work culture implemented by employees does not fully align with the rules and regulations in work enviroment, particularly related to the issue of employee absenteeism. One factor contributing to the work culture is the low awareness among employee about the importance of time discipline. Aims: The research aims to identify the influence of work culture on employee performance at KrembanganSelatan Community Health Center in Surabaya City. Methods: This was a quantitative method with a cross-sectional design. The sample consistend of 33 respondents out of population of 73 employees at KrembanganSelatan Community Health Center. The independent variable was work culture, and dependent variable was employee performance. Data was collected through a questionnaire, and analyzed using linear regression. Results: The research findings indicate that the significance value (Sig.) is 0,000 < 0,05, leading to the rejection of H0 and acceptance of Ha. The work culture was assessed as “Good” in 79% and “Fair” in 21%of cases. The employee performance was assessed as “Good” in 58% and “Fair” in 42% of cases. A good work culture determines employee performance, which will influence the achievement of organizational goals and the quality of sevices provided. Conclusion: Work culture has a significant effect on the performance of employees at KrembanganSelatan Community Health Center. That mean the better the work culture, the better the employee performance.